2016
DOI: 10.1016/j.rmed.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival in coexistent hypersensitivity pneumonitis with autoimmune features

Abstract: Background Hypersensitivity pneumonitis (HP), an immune-mediated inflammatory interstitial lung disease (ILD), can result from exposure to several well-recognized antigens. Despite antigen avoidance, progressive pulmonary fibrosis and death can occur, suggesting that additional factors may contribute to disease activity. We hypothesized that the presence of autoimmunity might impact clinical course in patients with HP. In this study, we examined an HP cohort to identify those with HP and autoimmune features (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 33 publications
4
47
1
1
Order By: Relevance
“…That threshold was selected because of its increased specificity and easy applicability in routine practice. Although germinal centers may be observed in IPF, CTD-ILD, and hypersensitivity pneumonitis, 19,2426 patients with CTD-ILD are described as having higher germinal center scores than do patients with IPF. 24 Furthermore, patients with hypersensitivity pneumonitis may have up to 2 germinal centers in one high-power field.…”
Section: Discussionmentioning
confidence: 99%
“…That threshold was selected because of its increased specificity and easy applicability in routine practice. Although germinal centers may be observed in IPF, CTD-ILD, and hypersensitivity pneumonitis, 19,2426 patients with CTD-ILD are described as having higher germinal center scores than do patients with IPF. 24 Furthermore, patients with hypersensitivity pneumonitis may have up to 2 germinal centers in one high-power field.…”
Section: Discussionmentioning
confidence: 99%
“…Some single-nucleotide polymorphisms (SNP) such as PD-1.1 G/A and PD-1.3 GA were found to be involved in the RA susceptibility4546. Moreover, previous studies also indicated that immune-mediated pneumonitis may be associated with autoimmune process4748. Animal experimental results demonstrated that pneumonitis was concomitant with RA and even shared the same immunity mechanism with RA4950.…”
Section: Discussionmentioning
confidence: 99%
“…Two chest radiologists (J.H. Chung and S. Montner) reviewed high-resolution computed tomography (HRCT) of patients with CHP, and characterised and scored them for features of fibrosis [ 11 ] (defined as the presence of reticulation, traction bronchiectasis and honeycombing). A systematic, detailed historical assessment of environmental antigen exposures (avian, mould, hot tub and unknown) is performed for all patients in the University of Chicago ILD registry, regardless of referring diagnosis.…”
Section: Methodsmentioning
confidence: 99%